The Relationship between Stress Levels and Excessive Daytime Sleepiness in Final Year Students of the Faculty of Nursing, University of Riau - Suri Yusufi Pratiwi; Darwin Karim; Tesha Hestyana Sari (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Final year students are prone to experiencing stress as a result of the pressure or burden they experience. Stressful conditions can cause sleep problems in individuals, one of which is Excessive Daytime Sleepiness. EDS is a feeling of excessive sleepiness during the day. The purpose of this study was to determine the relationship between stress levels and the incidence of Excessive Daytime Sleepiness in final year students of the Faculty of Nursing, University of Riau. This study uses a type of quantitative research with a correlation research design and a cross sectional approach. The study was conducted on 105 respondents, namely final year students at the Faculty of Nursing, University of Riau with a sampling technique using proportional random sampling. The research instrument used a questionnaire sheet. The analysis used was univariate and bivariate analysis using the Pearson Chi Square test. The results of the bivariate statistical test showed that there was a relationship between stress levels and the incidence of Excessive Daytime Sleepiness in final year students of the Faculty of Nursing, University of Riau with a p value of 0.000 Î± (0.05). There is a relationship between stress levels and the incidence of Excessive Daytime Sleepiness in students of the Faculty of Nursing, University of Riau. It is expected that students can control stressful events to avoid Excessive Daytime Sleepiness.